Cultural botany: a study of plant usage in Mandailing traditions in Kampung Mandailing Ayer Tawar Perak, Malaysia - Saipudin, Nur Adlin; Mat Nayan, Nadiyanti (2025)
The Mandailing community, originally from North Sumatra, migrated to Malaysia in the early 19th century, settling in Negeri Sembilan, Perak, and Selangor. They have preserved their rich heritage while blending some traditions with Malay culture. Their way of life is deeply tied to nature, relying on local vegetation for sustenance, health, and rituals. Key crops like rice, coffee, and fruit trees are integral to their agricultural practices and cultural identity. This study highlights the connection between Mandailing culture and vegetation, promoting awareness of their heritage and sustainable practices. It explores the cultural significance and practical uses of plants in traditional practices, ceremonies, and landscape architecture. Using qualitative methods, the research includes interviews with three respondents representing the Mandailing culture in Ayer to provide visions into the traditional uses and symbolism of specific plants. Based on thematic analysis there are several plants used by the Mandailing community in Ayer Tawar such as i) Food (Solanum torvum), ii) Medicinal (Akar Kayu), iii) Industry (Oryza sativa), and iv) Cultural services (Carica posoposa). These plants demonstrate their reliance on natural resources and the deep-rooted connection to their environment. The findings emphasize a harmonious integration of culture, tradition, and sustainability, offering valuable lessons for preserving cultural identity through vegetation.